Pengaruh Perdagangan Internasional Ekspor Dan Impor Terhadap Pertumbuhan Ekonomi Di Negara ASEAN: Studi Pada Negara Indonesia, Malaysia, Singapura Tahun 2013-2022 - Rika Kurnia; Zuha Lazuardi Muhammad Nafaris Al-Fath; Melita Sari; Muhammad Kurniawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the influence of international trade, exports and imports on economic growth in ASEAN countries. This research was conducted using international trade and economic growth data from ASEAN countries in the 2013-2022 period. The method used in this research is regression analysis to measure the relationship between export, import and economic growth variables. The data used is secondary data obtained from trusted sources such as reports from the Central Statistics Agency and Word Bank. The research results show that international export trade has a significant positive influence on economic growth in ASEAN countries. This shows that increasing exports can contribute to increasing economic growth in ASEAN countries. On the other hand, international import trade also has a significant positive influence on economic growth in ASEAN countries